Implications of sanitation for rural resident health: Evidence and mechanisms - Huang, Li; Chen, Shupeng; Wu, Heng; He, Yuhong; Zhou, Mi (Frontiers in Environmental Science, 2022)
This paper uses field survey data from rural areas of Liaoning Province, China to investigate the relationship between sanitation and the health of rural residents. The results show that the use of traditional latrine pits is significantly negatively correlated with health among rural residents. Robustness tests using Propensity Score Matching (PSM) further demonstrate the consistency of the results. Further research suggests that traditional latrine pits may affect the health of rural residents through the poor eating habits of rural residents and by polluting drinking water sources. Using the LSA method to estimate the health value of flush toilets, this study concludes that the health value of flush toilets in the sample area accounts for 98% of annual per capita household income.